The "secret elements" of musical performance (2013)
During the nineteenth century, the figures of the composer and the musical performer split, giving rise to various positions about the scope of the role of the performer, as well as about the conception of the musical work and the score as its graphic equivalent. This article reviews several of them in which, nevertheless, it finds a common element that all recognize: the “inevitable” contribution of the performer. Contribution that is defined in the terms that establish the so-called cognitive-enactive musical semiotics, gestures and performance studies, to determine the participation of the body, and especially of the corporeality inherent in the execution, as an instance of significance and, to at the same time, vehicle of communication of the musical meaning built.